Эгызоос: повестьёс / Петр Скобелев - Скобелев Петр Николаевич (Удмуртия, 2006)
Экземпляры: (20170113) / Инвентарный номер: 39670 / Цена: 50.00 / Сис.шифр: С(Удм) / Авт.знак: С 44 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)6